Education on Virtue in Islamic Educational Thought and Contemporary Western Philosophies - A Comparative Study - Aloqayli, Hailah Faisal (Journal of Educational and Psychological Sciences, 2024)
This study aimed to liberalize the concept of Education on Virtue in Islamic Educational Thought and to identify the most prominent features of virtue education, and identifying points of similarities and differences between its content in Islamic educational thought and contemporary Western philosophies.  This study approaching the comparative method alongside; And because the image of an idea and its value are appears when it measured against others. Therefore it compared the concept of virtue between the two thoughts by choosing (Peterson and Seligman) modle, as a common ground for this comparison, and clarifiy the Islamic point of view from Western philosophies in the education on virtue. This study was concluded in the seventh chapter, which contained the study's summary, findings, recommendations and proposals. Among its most prominent results were: 1.Most contemporary Western philosophies do not pay direct attention to virtue or ethical values, unless they aim at it implicitly; and that of course is due to the necessity of the moral aspect in human societies.And that abolition it theoriecaly, does not require to abolition it Realistically. 2.Contemporary Western philosophies does not agree with education on virtue in Islamic thought in all its aspects in concept and content, nor even with the model reached by Peterson and Seligman. in view of the fact that is concentrate an aspects and neglect other. in addition to generalization of circulate some pedagogical principles incurly. This is due to the scientific nature that dominates these philosophies. 3.One of the basic rules for Muslim educational scholars is to combine the scientific and practical side, , this result is one of the most prominent results of this study. As the perfection of virtue lies in the combination of the theoretical and the practical by making the practical results of the theoretical side.
Keywords: education; virtue; contemporary thought; comparison; philosophy